The Effect of Tax Sanctions and Tax Knowledge on Compliance with Motor Vehicle Tax Payments - Rizki; Andi Gisya Patika; Himmatul Ulyah (Jurnal Akuntansi dan Perpajakan, 2025)
Compliance in paying motor vehicle taxes is influenced by various factors, such as tax sanctions and tax knowledge. However, there are still issues related to tax sanctions, particularly the firmness of enforcement against taxpayers who violate regulations. Taxpayers' knowledge of taxation remains limited, especially in terms of understanding tax laws and procedures. This study aims to analyze the impact of tax sanctions and tax knowledge on compliance in paying motor vehicle taxes, particularly for two-wheeled vehicles. The method used is quantitative, with analysis through multiple linear regression to test the independent variables against the dependent variable, both partially and simultaneously, using SPSS version 25. This study utilizes both secondary and primary data through random sampling techniques, with a total of 100 respondents who own motor vehicles. The results of the study show that the tax sanctions variable does not influence compliance in paying motor vehicle taxes. However, tax knowledge has an effect on compliance in paying motor vehicle taxes.